La Guerra d’Etiopia, il Commonwealth e la crisi del sistema imperiale britannico - Di Rienzo, Eugenio (Studi Politici, 2025)
Italy’s invasion of Ethiopia in October 1935 marked a turning point in interwar Europe. The last great colonial conquest in Africa had enormous repercussions on European international relations. The British Government had felt constrained to support the Société des Nations, despite fears that sanctions through the League could lead to war with Italy. The concentration of the Royal Navy in the Mediterranean Sea distanced Mussolini from the Western Powers and placed the French government on the horns of dilemma: should France support its military partner, Italy, or its more important potential ally, Great Britain? Mussolini turned towards Nazi Germany in attempt to end his diplomatic isolation. The question of American adherence to sanctions increased the disagreements between British politicians and the Roosevelt administration in Washington, as each tended to blame the other for the failure of oil sanctions and the collapse of «collective security». The international crisis posed similarly thorny problems for the Commonwealth of Nations and determined the beginning of the irreversible crisis of the British Imperial System.